Pengembangan Aplikasi Distribusi Surat Di Fakultas Teknologi Informasi Dengan Notifikasi SMS Menggunakan Framework YII dan Gammu - Kamil, Husnil (JURNAL NASIONAL TEKNIK ELEKTRO, 2013)
Letter management system at Information Technology Faculty is still done manually. This method has some issues such as letter not archieved properly, late letter, letter was not received by the intended recipients and letters are damaged on distribution process. There is a need for a software that is able to manage and distribute a letter in Information Technology Faculty.Letter distribution software for Information Technology Faculty was developed by using Yii framework to build  web-based applications and Gammu SMS Gateway to equip the software with SMS notification feature. Framework utilization aims to speed up the software development process. This letter distribution software is also equipped with a feature that allows the user to comments a letter so they are able to interact with other users.The result of this research is a software that can be used to manage and distribute letter in Information Technology Faculty. This software was developed on ubuntu linux operating system as the server and apache as web server, PHP programming language and MySQL database. The software has not been used as operational software in Information Technology Faculty, but the software has met the basic functions of the letter distribution software for Information Technology Faculty.Key words : web application, letter, letter distribution, framework, Yii, SMS notification, Gammu, comment AbstrakSistem pengelolaan surat masuk di Fakultas Teknologi Informasi masih dilakukan secara manual. Pengelolaan secara manual ini menimbulkan beberapa permasalahan. Permasalahan tersebut antara lain arsip yang tidak terkelola dengan baik, surat terlambat sampai, surat tidak diterima dengan oleh penerima yang seharusnya dan surat yang rusak saat distribusi. Diperlukan sebuah perangkat lunak yang mampu mengelola dan mendistribusikan surat yang beredar di Fakultas Teknologi Informasi.Aplikasi distribusi surat di Fakultas Teknologi Informasi dikembangkan dengan menggunakan framework Yii untuk proses pengembangan aplikasi berbasiskan web dan Gammu untuk menambahkan fitur SMS Gateway. Penggunaan framework bertujuan untuk mempercepat proses pengembangan aplikasi. Aplikasi distribusi surat ini juga dilengkapi dengan fitur komentar yang memungkinkan pengguna dapat saling berinteraksi dengan pengguna lainnya. Penelitian ini menghasilkan sebuah aplikasi yang dapat digunakan untuk mengelola dan mendistribusikan surat di Fakultas Teknologi Informasi. Aplikasi ini dikembangkan pada sistem operasi ubuntu linux sebagai server dan menggunakan web server apache, bahasa pemograman PHP dan database MySQL. Aplikasi ini belum digunakan pada operasional Fakultas Teknologi Informasi namun aplikasi ini sudah memenuhi fungsi dasar aplikasi distribusi surat di Fakultas Teknologi Informasi.                                                                                                                                                        Key words : web application, letter, letter distribution, framework, Yii, SMS notification, Gammu, comment